Comprehensive bond values tables : showing net returns on bonds and other redeemable securities paying interest semiannually - Financial Publishing Company (Boston : Financial Publishing Company, 1958)
This 4th edition shows the complete range of quarter coupons and odd 1/8 coupons between 1% and 6%. This range and the corresponding range of yields from low to high, make the tables appropriate for general use today.
ucj 14/01/2019
Ref
Keywords: Bonds; Investments